The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1021/jp902322m
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Characterization of the Intermediates for Low-Temperature PROX Reaction of CO in H2—Oxidation of CO with OH via HCOO Intermediate

Abstract: / 2 O 2 f CO 2 ) on a FeO x /Pt/TiO 2 catalyst (∼140 wt % FeO x on 1 wt % Pt/TiO 2 ) was studied at 60°C by using in situ DRIFT spectroscopy. The PROX reaction of CO occurs via a HCOO intermediate and its oxidation with OH instead of oxygen, which is different from ordinary oxidation of CO with O 2 (CO + 1 / 2 O 2 f CO 2 ). The mechanism is as follows: (i) CO(a) + OH -f HCOO + e, (ii) O + e + H + f OH, and (iii) HCOO + OH f CO 2 + H 2 O, and step (iii) is the rate-determining step. Providing HCOO intermediates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 33 publications
3
63
1
Order By: Relevance
“…In the presence of H 2 , the surface of Au/TiO 2 catalyst was covered by H 2 O and OH groups in the oxidation of CO . A FTIR study of CO oxidation on FeO x /Pt inverse catalyst indicated that the surface OH species can directly react with the COOH to produce CO 2 . The DFT calculation suggested that the reaction of OH species with CO went through a smaller barrier compared to the reaction CO + O → CO 2 on metal based catalyst .…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of H 2 , the surface of Au/TiO 2 catalyst was covered by H 2 O and OH groups in the oxidation of CO . A FTIR study of CO oxidation on FeO x /Pt inverse catalyst indicated that the surface OH species can directly react with the COOH to produce CO 2 . The DFT calculation suggested that the reaction of OH species with CO went through a smaller barrier compared to the reaction CO + O → CO 2 on metal based catalyst .…”
Section: Discussionmentioning
confidence: 99%
“…The strong band near 2048 cm À1 is assignable to linear CO species on the Pt surface, [12,16] which is slightly shifted to lower frequency than that obtained under a flow of pure CO (2085 cm À1 , Figure S5) probably as a result of lower CO coverage. [17,18] The band at 3278 cm À1 resulted from the formation of H 2 O. Moreover, bands at 2978, 1730, and 1421 cm À1 can be assigned to physical adsorption of formic acid on the MCM-41 surface, [19] while two other bands at 2941 and 1574 cm À1 are attributed to adsorption of formate species on MCM-41 ( Figure S6c).…”
Section: Methodsmentioning
confidence: 98%
“…7 On the other hand, various studies have shown that H 2 promotes low-temperature CO oxidation, although the promotion mechanism is under debate. [8][9][10] Previously, we reported that Ir-Fe/SiO 2 catalyst is highly active and selective for the PROX reaction. 11 Compared with Ir/SiO 2 , the addition of Fe not only weakens the adsorption of CO or H 2 on the Ir sites, but also greatly increases the adsorption of O 2 on the FeO x sites.…”
Section: Introductionmentioning
confidence: 99%